The Influence of Sustainability-Driven Budgeting on Operational Efficiency and Competitive Advantage - Eko Wiji Pamungkas; Dini Fitriani (PT. Anagata Sembagi Education, 2026)
Global pressure for sustainable business practices has encouraged firms to integrate sustainability principles into their budgeting systems as part of strategic management. Sustainability-driven budgeting is increasingly viewed not merely as a compliance mechanism, but as a potential driver of operational efficiency and competitive advantage. This study aims to examine the effect of sustainability-driven budgeting on operational efficiency and competitive advantage, as well as to test the mediating role of operational efficiency in this relationship. A quantitative explanatory survey design was employed. Data were collected from 210 managerial respondents directly involved in budgeting and strategic decision-making processes and analyzed using Partial Least Squares Structural Equation Modeling. The results reveal that sustainability-driven budgeting has a positive and significant effect on operational efficiency. Operational efficiency, in turn, significantly influences competitive advantage. Mediation analysis confirms that operational efficiency partially mediates the relationship between sustainability-driven budgeting and competitive advantage. These findings indicate that sustainability-oriented budgeting practices can generate strategic value by enhancing internal efficiency while strengthening firms’ long-term competitive positioning. This study contributes to the literature on business sustainability by highlighting budgeting as a core managerial mechanism and offers practical insights for managers in designing performance-oriented and sustainability-based budgeting policies.